The Influence Of Cooperative Learning Models And Learning Motivation On Student Learning Outcomes On Chemical Bond Material - Yonni Sepriani Tampubolon; Ajat Sudrajat (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This study aims to analyze the influence of cooperative learning models and learning motivation on student learning outcomes on chemical bonding materials. The background of this research is the low learning outcomes of students on complex chemical materials, especially chemical bonds, which are often caused by a lack of understanding of concepts and low student learning motivation. To overcome this problem, a cooperative learning model is proposed as an effective strategy. This study uses a quantitative method with a pseudo-experimental design involving two classes as samples: an experimental class that uses a cooperative learning model and a control class with conventional learning methods. Data collection was carried out through learning outcome tests and learning motivation questionnaires. The study results show that the cooperative learning model positively and significantly influences student learning outcomes. In addition, it was found that student learning motivation plays a role as a moderation variable that strengthens the impact of learning models on learning outcomes. In conclusion, using cooperative learning models effectively improves student learning outcomes, especially when combined with efforts to increase learning motivation. Therefore, this learning model is recommended for chemistry learning, especially in chemical bonding materials.